Prosocial Behavior of Elementary School Students and Factors That Affect Them - Nonitasari, Ipon (Pedagogik Journal of Islamic Elementary School, 2020)
This research has the aim of knowing the form of prosocial behavior of students and the factors that influence the prosocial behavior of elementary school students. This research uses a qualitative approach with case study methods. Participants or objects of this study are grade IV students and teachers (class guardians). Data collection techniques use observation, interviews, and documentation. Analyze the data in this study with data reduction, data presentation, and conclude. The validity of the data in this study uses triangulation. The results of this study show that the prosocial behavior that appears in class IV students in elementary school includes honesty, helping, sharing, generosity, and cooperating. The form of prosocial behavior in each student differs from factors such as 1) the stage of child development which includes physical skills, knowledge insights (cognitive), emotional and moral social 2) learning strategies used by teachers such as guidance and motivation, giving direct commands, providing examples of prosocial behavior in each school activity, through fairy tales or reading stories, songs or videos, and role-playing activities, and 3) environmental factors include the family environment, peer interaction, education system, and school culture.